Ketersediaan ruang terbuka hijau di Kota Denpasar dan strategi pengelolaannya - Indrawati, Mei; Sudiana, A.A. Ketut; Sumantra, I.K (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Green open space (GOS) plays a very important role in realizing a sustainable city and has a balance of ecological and psychological functions for urban communities. Green open space (GOS) can be divided into two categories, namely public GOS and private GOS, but only public GOS can still be controlled directly by the government. Until now, there has been no study regarding the use of public green open spaces in Denpasar City. The aim of this research is to identify the availability of public green open space in Denpasar City, analyze the implications of using public green open space in Denpasar City, and formulate strategies and policies for managing public green open space in Denpasar City. Data collection techniques in this research were interviews and questionnaires. The data analysis techniques in this research are qualitative and quantitative descriptive analysis techniques to determine the availability of public GOS, SWOT analysis for the use of public RTH, and Analytical Hierarchy Process (AHP) to determine management strategies and policies. The availability of public green open space in 2011 was recorded at 2,341.48, or 18.32 percent. The availability of public green open space in 2019 was recorded at 1,572,990 hectares, or 12.49 percent. The difference between 2011 and 2019 was 768,490 ha, or 5.83 percent. The minimum area of public green open space in accordance with the regulations, namely 20 percent, was 1.68 percent in 2011 data and 7.51 percent in 2019 data. The implementation of the utilization of Denpasar City Public Green Open Space (GOS) based on the results of the analysis that has been carried out does not comply with the standards of Minister of Home Affairs Regulation Number 1 of 2007 concerning Arrangement of Green Open Space in Urban Areas and Minister of Public Works Regulation Number 5 of 2008 concerning Guidelines for Providing and Utilizing Green Open Space in Urban Areas. Management still needs to be improved both in terms of handling, security, and maintenance as well as maintaining the availability of existing public open space.